Japan's american interlude - Kawai, Kazuo (University of Chicago Press, 1960)
How did the Japanese themselves respond to the American occupation? How were the sweeping reforms—political, social, and economic—of SCAP's program received? How permanent was their effect, and why did some succeed and others fail completely? How successful in the long view was the democratization induced by MacArthur's "artificial revolution"? And what tendencies existing in fundamental Japanese attitudes and history might account for this peculiar success? The author, Japanese-born and educated in America, a political scientist and journalist, brings his unique experience and knowledge to bear on these questions. The result is a book which tells the story of the American occupation of Japan from the Japanese point of view.